Review paperNeural stem cell therapy in neurological diseases - Uyanikgil, Yigit; Balcioglu, Huseyin Avni (Archives of Medical Science, 2009)
Early developmental process of mammalian embryo is almost completely directed by the behavior of stem cells, which is controlled by both environmental and intrinsic factors. These cells commonly subject to dividing, migration, deterioration or death. Comparing to all other tissues in the body, central nervous system has a considerably limited capacity to regenerate. Recent knowledge on neural stem cells has brought novel approaches as to the use of stem cells in the treatment of some neurodegenerative disorders such as Parkinson, Alzheimer disease and amyotrophic lateral sclerosis, as well as in the management of spinal cord injuries. However, scientific literature requires detailed information regarding the proliferation and differentiation of stem cells and the mechanisms controlling the migration of these cells to the targeted central nervous system site. Development of new therapeutic protocols using stem cells and their effective clinical application in the future would bring light to cope with a number of systemic diseases, especially neurological disorders. This review has considered the biological features of stem cells, stem cell plasticity, potential application of stem cells in neurological diseases and cancer, highlighting the promises as well as the problems of this treatment approach.